Pengujian Rekomendasi Pemupukan Spesifik Lokasi dan Sistem Tanam terhadap Hasil Padi Sawah di Desa Temega, Kecamatan Abang, Karangasem - PUJA, I NYOMAN; ATMAJA, I WAYAN DANA; SUMARNIASIH, MADE SRI (Agrotrop : Journal on Agriculture Science; Vol 9 No 1 (2019), 2019)
Evaluation of Specific Location Fertilizer Recommendations and Plant System on Rice Yield T emega Village, Abang District, Karangasem . This study aims to determine the response of specific location fertilizer recommendations and planting system on rice yields in Temega Village, Abang District, Karangasem Regency. The method was used Factorial Randomized Block Design (RBD). The treatment tried consisted of two factors. The first factor was fertilization recommendations (R): R 1 = location specific recommendation (250 kg Urea/ha, 100 SP36/ha and 50 kg KCl/ha); R 2 = Location specific recommendation + Compost (230 kg Urea/ha, 100 SP36/ha, 50 kg KCl/ha + 5 t compost/ha), R 3 = Farmer method (300 kg Urea/ha, 125 SP36/ha and 75 kg KCl/ha). The second factor was planting system (TL) : T = Tegel (20 cm x 20 cm) and L = Jajar Legowo 2 : 1. Combination of treatments into 6 treatments and each treatment was replicated 4 times so that there were 24 plots of research. The results showed that location specific fertilizer recommendations resulted in oven dry grain weight m -2 of 0.84 kg compare to that of farmers (0.85 kg). The application of location specific fertilizer recommendations can save as much as 50 kg Urea/ha, 25 kg SP36/ha and 25 kg KCl/ha. Jajar Legowo planting system can produce grain contain m -2 of 1.14 kg or an increase of 78.13% compared to tegel planting system (0.64 kg).